IMPLEMENTASI PERATURAN DAERAH NOMOR 36 TAHUN 2013 TENTANG PENATAAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI RUANG TERBUKA HIJAU KM 10 KOTA SORONG - Tri Rahmawati; Hafsawiyah Febriyanti Nurjannah (Muadalah : Jurnal Hukum, 2023)
Street vendors are business actors who complete their business activities within a certain period of time and use places to sell that are easily moved, such as on sidewalks. The increasing number of street vendors has reduced the unemployment rate in the surrounding area, but on the other hand their activities have disrupted the management of urban green open spaces. City green open spaces are areas where plants grow which are part of urban planning, and function to maintain urban green ecosystems, as stated in the Regional Regulation of the City of Sorong Number 36 of 2013 concerning Arrangement and Development of Street Vendors. However, this regulation has not been implemented properly. Although the street vendors are granted the right by the local authorities to build a permanent or semi-permanent place of business in the designated area. However, in reality there are still many street vendors who build their place of business by utilizing the sidewalk or roadside. This is what interferes with the arrangement and management of green open spaces in the city of Sorong